Legal status and the criminal activity of immigrants - Giovanni Mastrobuoni; Paolo Pinotti (W.E. Upjohn Institute for Employment Research, 2014)
We exploit exogenous variation in legal status following the January 2007 European Union enlargement to estimate its effect on immigrant crime. We difference out unobserved time-varying factors by 1) comparing recidivism rates of immigrants from the "new" and "candidate" member countries and 2) using arrest data on foreign detainees released upon a mass clemency that occurred in Italy in August 2006. The timing of the two events allows us to set up a difference-in-differences strategy. Legal status leads to a 50 percent reduction in recidivism and explains one-half to two-thirds of the observed differences in crime rates between legal and illegal immigrants.
Keywords: F22; K42; C41; 330; immigration; crime; legal status